Wnt signaling activation induces CTCF binding and loop formation at cis-regulatory elements of target genes - Nordin, Anna; Chakraborty, Chaitali; Jonasson, Mattias; Dano, Orgena; Zambanini, Gianluca; Pagella, Pierfrancesco; Remeseiro, Silvia; Cantù, Claudio (Genome Research, 2025)
Wnt signaling plays a pivotal role during development and homeostasis. Upon pathway activation, CTNNB1 (also known as beta-catenin) drives the expression of target genes from regulatory regions bound by TCF/LEF transcription factors. Gene regulation, however, entails the interplay between sequence information and 3D genome structure, yet the impact of Wnt signaling on genome structure has been poorly explored. Here, we investigate how Wnt signaling influences CTCF and cohesin, key regulators of 3D genome organization. We identify a series of novel CTCF binding sites that emerge upon Wnt stimulation: CTCF Redistributions Under Wnt (RUW). RUW sites are characterized by CTCF, cohesin, and TCF/LEF occupancy, and are dependent on beta-catenin. Beta-catenin and CTCF colocalize upon pathway activation, and disruption of selected binding sites perturbs target gene regulation. Moreover, Wnt signaling reorganizes the 3D genome as evidenced by genome-wide alterations in CTCF-bound loops. This work reveals a previously unexplored role for CTCF in the regulation of Wnt signaling.
10.1101/gr.279684.124